Effect of Oral Propranolol on Labor Induction - Direkvand-Moghadam, ashraf; Delpisheh, ali; Yousefinezhad, fahimeh; Jaafarpour, molouk; Ashrafi Hafez, asghar (Advances in Nursing & Midwifery, 2014)
Abstract Background and aim: Prolonged pregnancy increases the maternal and fetal morbidity and mortality. In order to avoid these complications and to manage prolonged pregnancies, different methods are used. The goal of this study was to evaluate the effect of oral propranolol on labor induction in nulliparous women with prolonged pregnancy. Material and Methods: A double blind randomized controlled trial was performed on 146 nulliparas women with a gestational age of 40–42 weeks of pregnancy. Participants were allocated into two groups of propranolol (a combination of oral propranolol and oxytocin) versus placebo (oxytocin and placebo). In propranolol group, 20 mg oral propranolol was placed into the empty capsule and administered immediately before induction. Placebo group received a similar appearance capsules containing starch. Administration was continued every 8 hours until obtained the good contractions. The induction with oxytocin was initiated similar in two groups. The mean duration for obtaining good contractions and Apgar scour was determined. Data were analyzed by SPSS and used descriptive statistics, t test, x2 and exit Fisher test. Results: Demographic and obstetric parameter were similar in both groups (p>0.05). Start of good contraction was different between groups in first and second day. In the first day of induction, Mean ± SD start of good contractions were 190.3 ± 21.4 and 176.2± 11.2 in propranolol group and placebo group consecutively (p<0.05). In the second day of induction, Mean ± SD start of good contractions were 113.5 ± 9.2 and 185 ± 26.8 in propranolol group and placebo group consecutively (p < 0.001). Conclusion: Oxytocin combined with oral propranolol can decrease the time needed for start of good contraction in postdate pregnancy. Kay words: Induction, oral propranolol, prolonged pregnancy REFERENCES Adamsons K de la Vega A. & Santiago P(1999). Reduction in the cesarean section rate in nulliparous patients after administration of intravenous propranolol. P uerto R ico Health Science Journal 18(1) 5-8. Alexander J M Mcintire D D. & Leveno K J (2000) Forty Weeks and Beyond: Pregnancy Outcomes by Week of Gestation. Obstetrics and Gynecology .96(2) 291-4. Bennett K A Crane J M O’shea P Lacelle J Hutchens D & Copel J A (2004) First Trimester Ultrasound Screening Is Effective in Reducing Postterm Labor Induction Rates: A Randomized Controlled Trial. American Journal of Obstetrics and Gynecology 190(4)1077-81. ACOG Committee on Practice Bulletins-Obstetrics (2004) Clinical Management Guidelines for Obstetricians-Gynecologists. Number 55, September 2004 (replaces practice pattern number 6, October 1997). Management of Postterm Pregnancy. Obstetrics and Gynecology . 104(3) 639-46. Caughey A B Musci T. J(2004) Complications of term pregnancies beyond 37 weeks of gestation. Obstetrics and Gynecology . 103(1) 57-62. Chanrachakul B. et al(2003) Reduced expression of immunoreactive beta2-adrenergic receptor protein in human myometrium with labor. The Journal of Clinical Endocrinology and Metabolism . 88(10) 4997-5001. Cotziaz C S Paterson-Brown S & Fisk N M (1999) Prospective Risk of Unexplained Stillbirth in Singleton Pregnancies at Term: Population Based Analysis. BMJ .19(7205) 287-8. Hannah M(1993) Postterm Pregnancy: Should All Women Have Labour Induced? A Review of the Literature. Fetal and Maternal Medicine Review . 5 (1)19-27. Hilder L Costeloe K. & Thilaganthan B (1998) Prolonged Pregnancy: Evaluating Gestation-Specific Risks of Fetal and Infant Mortality. British Journal of Obstetrics and Gynaecology . 105(2) 169-73. Kashanian M Fekrat M. Zarrin Z. & Ansari N(2008) A Comparison between the Effect of Oxytocin Only and Oxytocin Plus Propranolol on the Labor (A Double Blind Randomized Trial). The Journal of Obstetrics and Gynaecology Research . 34(3) 354-8. Laursen M Bille C Olesen AW Hjelmborg J Skytthe A, Christensen K (2004) Genetic Influence on Prolonged Gestation: A Population-Based Danish twin Study. American Journal of Obstetrics and Gynecology . 190(2) 489-94. Norwitz E R Snegovskikh V V & Caughey A B (2007) Prolonged Pregnancy: When Should We Intervene? Clinical Obstetrics and Gynecology . 50(2) 547-57. Oskouei S Ramezanikh F Taavoni S Haghani H (2004) [Assessment of the predisposing factors of prolonged pregnency]. Iran Journal of Nursing (IJN).17(38)25-31.(Persian) Palomäki O Uotila J Tammela O et al (2006) A Double Blind, Randomized Trial on Augmentation of Labour with a Combination of Intravenous Propranolol and Oxytocin Versus Oxytocin Only. European Journal of Obstetrics, Gynecology and Reproductive Biology . 125 (1) 44-9. Perry M Y Leaphart W L(2004). Randomized Trial of Intracervical Versus Posterior Fornix Dinoprostone for Induction of Labor. Obstetrics and Gynecology . 103(1) 13-7. Sanches-Ramos Lquilien M & Kaunitz A(1996) Ranomized Trial of Oxytocin alone and with Propranolol in the Management of Dysfunctional Labor. Obstetrics and Gynecoogy . 88(4 pt) 517-520 Savitz DA Terry JW Jr Dole N Thorp JM Jr Siega-Riz AM Herring (2002) Comparison of Pregnancy Dating by Last Menstrual Period, Ultrasound Scanning, and their Combination. American Journal of Obstetrics and Gynecology . 187(6) 1660-6. Smith Y R Dombrowski M P Leach K C. & Hurd W W (1995) Decrease in Myometrial Beta-Adrenergic Receptors with Prenatal Cocaine Use. Obstetrics and Gynecoogy . 85(3) 357-60. Stotland N E Washington A E & Caughey A B(2007) Prepregnancy Body Mass Index and the Length of Gestation at Term. American Journal of Obstetrics and Gynecology . 197(4) 378 e1-5. Taipale P. & Hillesmaa V(2001) Predicting Delivery Date by Ultrasound and Last Menstrual Period in Early Gestation. Obstetrics and Gynecology . 97(2) 189-94. Usha Kiran T S Hemmadi S Bethel J & Evans J (2005) Outcome of Pregnancy in a Woman with an Increased Body Mass Index. BJOG , 112(6) 768-72